Brief overview of measures related to work-life balance in the European Union: country sheets - Ghailani, Dalila (Brussels, 2018)
"After the withdrawal of the Maternity Leave Directive, the Commission decided to take a broader approach to addressing women's underrepresentation in the labour market. The 'New Start' initiative to address the work-life balance challenges faced by working parents and carers, presented in April 2017 as the first legislative deliverable of the European Pillar for Social Rights, takes into account the developments in society over the past decade, aiming to enable parents and other people with caring responsibilities to better balance their work and family lives, and to encourage a better sharing of caring responsibilities between women and men. As part of the follow-up to the European Commission initiative, the ETUI and the ETUC asked the European Social Observatory to provide a brief overview of measures related to work-life balance in the 28 European Member States and to map the compliance with the proposals in the Directive. After the presentation of this overview the Monthly forum will provide the opportunity to debate the Commission proposal and the possible ways forward."